1994
DOI: 10.1016/0166-445x(94)90009-4
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between copper and cadmium during single and combined exposure in juvenile tilapia Oreochromis mossambicus: Influence of feeding condition on whole body metal accumulation and the effect of the metals on tissue water and ion content

Abstract: Aquatic Toxicology 30 (1994) 117-135 ; Interactions between copper and cadmium during single and combined exposure in juvenile tilapia O r e o c h r o m i s m o s s a m b i c u s :Influence of feeding condition on whole body metal accumulation and the effect of the metals on tissue water and ion content AbstractJuvenile tilapia (Oreochromis mossamhicus) were exposed for 96 h to ranges of sublethal concentrations of Cu or Cd, under both fed and non-fed conditions. Exposure to one metal (Cu or Cd) not onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
2
2

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 35 publications
3
23
2
2
Order By: Relevance
“…Exposure of the fish to Cu and Cd, both singly and combined, did not affect the water content of any of the organs studied, which contrasts with previous results on juvenile tilapia exposed to identical metal regimes (Pelgrom et al, 1994a). This may relate to an increased sensitivity of younger life-stages to osmoregulatory disturbances, i.e.…”
Section: Water Contentcontrasting
confidence: 95%
See 4 more Smart Citations
“…Exposure of the fish to Cu and Cd, both singly and combined, did not affect the water content of any of the organs studied, which contrasts with previous results on juvenile tilapia exposed to identical metal regimes (Pelgrom et al, 1994a). This may relate to an increased sensitivity of younger life-stages to osmoregulatory disturbances, i.e.…”
Section: Water Contentcontrasting
confidence: 95%
“…Previously, we demonstrated Cu-Cd interactions on whole body metal accumulation during waterborne metal exposure of juvenile tilapia (Pelgrom et al, 1994a). Data in the present study show that interactions observed are organ specific and therefore data for most organs are not representative for the whole organism.…”
Section: Gonadscontrasting
confidence: 69%
See 3 more Smart Citations